The Development of Higher Education Establishment Autonomy in Latvia - Mihailovs, Ivans Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The events, which were highly important for Latvian higher education development, were happened in the 1st part of 2011, incl. discussions about higher education establishment (university) autonomy frames and content. According to the national legislation and higher education establishment statuses, autonomy is mostly centred to the “inside” of the higher education establishment, bringing in “outside” duties to respect and comply with state regulation and standards etc. The analysis of current situation in Latvian higher education shows, that there are four models of autonomy, which have differences in legal regulation, management and daily practise. Also the targets of the founders, the priorities of educational activities are different and exactly influence educational relations, content of studies, study requirements, students, staff and administration duties and rights. In this context, discussions about the founder’s rights to supervise higher education establishment work and harmonization of society-statehigher education establishment still are opened for adjustment.